Vulnerability or resilience? Examining trust asymmetry from the perspective of risk sources under descriptive versus experiential decision - Zhu, Jingyuan; Yao, Yingying; Jiang, Shan (Frontiers in Psychology, 2023)
Introduction The investigation of trust vulnerability is important to the understanding of the potential mechanisms of trust formation and erosion. However, more effective exploration of trust vulnerability has been hindered due to the lack of consideration of risk sources and types of information. Methods This study extended the investigation of asymmetry to both social and natural risk under experiential and descriptive decisions. Using the trust game as the decision-making paradigm and money as the subject matter, the research employed experimental methods to examine how people perceive and make decisions after being positively and negatively affected by natural and social risks. A total of 286 college students were participated in our study. Study 1 (n = 138) and Study 2 (n = 148) explored asymmetry in experiential and descriptive decision separately. Results The findings indicated that when considering experiential information, negative information had a greater effect in reducing trust compared to the enhancing effect of positive information (t = −1.95, p = 0.050). Moreover, the study revealed that negative information had a stronger negative impact in the context of social risks rather than natural risks (t = −3.26, p = 0.002), suggesting that trust is vulnerable both internally and externally. Conversely, when considering descriptive information, the effect of both positive and negative information on trust was symmetrical, and the impact of negative information was less significant compared to that of natural risks, indicating that trust has a certain level of resilience (t = 2.25, p = 0.028). Discussion The study emphasizes the importance of refining risk sources and information characteristics in complex scenarios in order to improve understanding of trust enhancement and repair.